Design of non-polarizing cut-off filters based on dielectric-metal-dielectric stacks - Cai, Qing-Yuan; Luo, Hai-Han; Zheng, Yu-Xiang; Liu, Ding-Quan (Optics express, 2013)
Cut-off filters are usually operating at oblique incidence and exhibit polarization dependence properties. We propose a simple approach to design cut-off filters with low linear polarization sensitivity (LPS) based on dielectric-metal-dielectric (DMD) stacks. The designing method is derived from the theory of optical film characteristic matrix. The admittance loci of the film are adjusted to achieve similar spectral properties of s- and p-polarized light at oblique incidence. Different film structures are designed non-polarizing at different angles of incidence with the method. The results show that the designing method is efficient for designing non-polarizing cut-off filters, which are widely used in non-polarizing optical system.